Analisis Penerapan Akuntansi Sederhana pada Usaha Mikro Food and Beverages survei pada Usaha Mikro Katering Dua Putra - Dianita, Mirna; Tresnawati, Rina; Hadian, Niki; Prayitno, Yogo Heru; Rachman, Yoga Tantular (Universitas Galuh, 2024)
Financial management is an important element in a company's progress. One way to manage finances is through accounting practices, which is a systematic process for producing financial information that is relevant for decision making. Micro, Small and Medium Enterprises (MSMEs), especially micro enterprises, generally still use money as a transaction medium, it is important for them to utilize accounting practices. Accounting can provide significant support in managing MSME finances, assist in planning to increase profits, and ultimately encourage the growth of MSMEs so that they can become stronger contributors in improving the Indonesian economy. However, many MSMEs do not fully utilize accounting in their business operations. Therefore, MSMEs need understanding and awareness of the preparation of effective financial reports. The method in this research uses a descriptive method, describing the problems found and providing solutions to these problems. The results of this research provide direction and an overview of the preparation of simple financial reports for MSMEs, especially micro businesses, so that they can be implemented in their businesses. Apart from that, this research provides an overview of the importance of implementing and understanding even simple accounting in business management and efforts to maintain business sustainability and business development.